A Set-Based Optimal Control Approach for Pharmacokinetic/Pharmacodynamic Drug Dosage Design. Issue 7 (2016) - Lucia, Sergio; Schliemann-Bullinger, Monica; Findeisen, Rolf; Bullinger, Eric
Abstract: Robust optimal control of pharmacokinetic/pharmacodynamic (PK/PD) models allows for optimal drug dosage design under model uncertainties. Typical PK/PD models are highly uncertain and therefore a robust design of the drug dosage is necessary to guarantee that important health-related constraints are satisfied for all the possible values of the uncertainty. This paper shows that the responses of a simple class of PK/PD models are monotonous in the parameters and in the input. This greatly simplifies the design of a scenario-based nonlinear model predictive controller as just two scenarios are necessary to fully bound the system responses. This is illustrated with the drug dosage design for a model of erythropoietin injection, in which we also show the potential benefit of having intermediate measurements during the application of the therapy.